Structural analysis of premolar roots in Middle Pleistocene hominins from China. Issue 136 (November 2019) - Pan, Lei; Dumoncel, Jean; Mazurier, Arnaud; Zanolli, Clément
Abstract: This study investigates permanent maxillary and mandibular premolar root structural organization in East Asian Middle Pleistocene hominins. In addition to reporting and analyzing the linear and volumetric properties of the roots, we used a landmark-free approach to both qualify and quantify in 3D premolar root shape variation of Middle Pleistocene hominins in East Asia. Moreover, we focus on some mid-to late East Asian Middle Pleistocene hominin specimens whose taxonomic attribution is unclear. We find considerable cementum in this sample of hominins, similar to other fossil groups, but clearly different from modern humans which have a very small amount of cementum. Additionally, a smaller root pulp cavity is found in later Homo (Neanderthals and modern humans). Our analyses on the crown-root surface area ratio show that East Asian Middle Pleistocene Homo erectus as well as one late Middle Pleistocene Homo sp. specimen (PA 81 P4 from Changyang site) are distinguished from other fossil and extant groups by a relatively larger root surface, stout root branches and thick cementum deposits. This may represent a distinct East Asian H. erectus dental pattern. Geometric morphometric analyses on the external root surface reveal a general trend of shape simplification along the Homo lineage examined here, and distinguish Early Pleistocene Homo, Middle Pleistocene H. erectus, Neanderthals and modern human morphologies. The late Middle Pleistocene teeth from Changyang site (PA 76 P 3 and PA 81 P 4 ) are close to East Asian H. erectus and Neanderthals, while the mid-Middle Pleistocene P3 from Panxian Dadong falls within the modern human distribution. Combined with dental crown morphology and root number/form reported in previous studies, our results show that the external root shape can be considered a taxonomically relevant indicator. In general, an evolutionary tendency towards modern human morphology is observed in part of the East Asian Middle Pleistocene specimens, while a retention of primitive, H. erectus -like features is expressed in some late Middle Pleistocene specimens, supporting a multi-lineage and discontinuous scenario of human settlements in East Asia.